PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP KENAKALAN REMAJA PADA SISWA SISWI KELAS X DAN XI DI SMAN TUAH GEMBILANG KECAMATAN BATANG TUAKA KABUPATEN INDRAGIRI HILIR - Jamilah, Jamilah; Zahirman, Zahirman; Supenteri, Supenteri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract:his research was conducted to determine the effect of parents' socioeconomic status on juvenile delinquency in class X and XI students at Tuah Gembilang High School, Batang Tuaka Subdistrict, Indragiri Hilir Regency. The population in this study amounted to 237 people with a sample of 45 people based on the author's consideration that only concerned can provide information / information in accordance with the level of social status they occupy. Quantitative descriptive data collection techniques were analyzed using descriptive explanations and simple liner tests with the help of SPPS version 21. The results of the study address the percentage of respondents obtained answers to how high the influence of parents' socioeconomic status on juvenile delinquency, the first was high socioeconomic status on juvenile delinquency that was 72.77, the second was moderate socioeconomic status of 48.05, and the last is low socioeconomic status, 56.33. From the results of a simple liner with the help of SPPS version 21 it is known that R square of 0.76.7 means that there is an influence of socioeconomic status on adolescent wearKey Words: Socio-Economic Status, Juvenile Delinquency